Highly‐accelerated Bloch‐Siegert |B1+| mapping using joint autocalibrated parallel image reconstruction. Issue 4 (1st July 2013) - Sharma, Anuj; Tadanki, Sasidhar; Jankiewicz, Marcin; Grissom, William A
Abstract Purpose To reconstruct accurate single‐ and multichannel Bloch–Siegert transmit radiofrequency (<alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgg4t0ftcvc" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />|B1+|</alternatives>) field maps from highly accelerated data. Theory and Methods The approach is based on the fact that the <alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgg4t0ftcwx" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />|B1+|</alternatives>‐to‐phase encoding pulse for each transmit coil and off‐resonance frequency applies a unique phase shift to the same underlying image. This enables joint reconstruction of all images in a Bloch–Siegert acquisition from an augmented set of virtual receive coils, using any autocalibrated parallel imaging reconstruction method. Results Simulations with an eight channel transmit/receive array head coil at 7T show that accurate <alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgg4t0ftcxg" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />|B1+|</alternatives> maps can be produced at acceleration factors of 16× and 6× for Cartesian and spiral sampling, respectively. A phantom experiment with a six channel transverse electromagnetic (TEM) transceive array coil allowed accurate reconstruction at 16× acceleration. 7T in vivo experiments performed using 32 channel receive and two‐channel transmit coils further demonstrate the proposed method's ability to produce high‐quality <alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgg4t0ftcz1" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />|B1+|</alternatives> maps at accelerations of 32× and 8× for Cartesian and spiral trajectories, respectively. Reconstruction accuracy is improved using disjoint k‐space sampling patterns between acquisitions. Conclusion The proposed approach allows high acceleration factors in Bloch–Siegert <alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgg4t0ftd6d" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />|B1+|</alternatives> mapping and can significantly reduce the scan time requirements for mapping the <alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgg4t0ftd7z" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />|B1+|</alternatives> fields of transmit arrays. Magn Reson Med 71:1470–1477, 2014. © 2013 Wiley Periodicals, Inc.